2018
DOI: 10.3389/fnins.2018.00461
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Studies Reveal the Subtle Difference Among Social Network Size Measurements and Shed Light on New Directions

Abstract: Social network size is a key feature when we explore the constructions of human social networks. Despite the disparate understanding of individuals’ social networks, researchers have reached a consensus that human’s social networks are hierarchically organized with different layers, which represent emotional bonds and interaction frequency. Social brain hypothesis emphasizes the significance of complex and demanding social interaction environments and assumes that the cognitive constraints may have an impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Given the stable individual differences in SNS, the neural bases of SNS and its behavioral relevance (e.g., personality and social cognition) may be manifested in the structural and functional variables, which could be detected by structural magnetic resonance imaging (MRI) and resting state functional MRI (rs-fMRI; DeYoung, 2010; Mar et al, 2013). Consistent with the social brain hypothesis (Dunbar, 2012;Liu et al, 2018;Mars et al, 2012), structural MRI studies have found correlation between the self-reported SNS and grey matter volume/density of the brain regions subserving social behaviors, including the amygdala (Bickart et al, 2011;Liu et al, 2018;Von Der Heide et al, 2014), ventromedial prefrontal cortex (vmPFC; Lewis et al, 2011;Noonan et al, 2018), superior temporal sulcus (STS; Kanai, Bahrami, Roylance, et al, 2012), precuneus (Noonan et al, 2018), and orbitofrontal cortex (Lewis et al, 2011;Von Der Heide et al, 2014).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Given the stable individual differences in SNS, the neural bases of SNS and its behavioral relevance (e.g., personality and social cognition) may be manifested in the structural and functional variables, which could be detected by structural magnetic resonance imaging (MRI) and resting state functional MRI (rs-fMRI; DeYoung, 2010; Mar et al, 2013). Consistent with the social brain hypothesis (Dunbar, 2012;Liu et al, 2018;Mars et al, 2012), structural MRI studies have found correlation between the self-reported SNS and grey matter volume/density of the brain regions subserving social behaviors, including the amygdala (Bickart et al, 2011;Liu et al, 2018;Von Der Heide et al, 2014), ventromedial prefrontal cortex (vmPFC; Lewis et al, 2011;Noonan et al, 2018), superior temporal sulcus (STS; Kanai, Bahrami, Roylance, et al, 2012), precuneus (Noonan et al, 2018), and orbitofrontal cortex (Lewis et al, 2011;Von Der Heide et al, 2014).…”
Section: Introductionmentioning
confidence: 83%
“…Better social abilities and larger network size may help humans to cooperate with each other (Tomasello, 2001). Research on human's social networks has expanded greatly in the sociological and psychological fields, and it has been shown that different factors may result in individual differences of social network size (SNS; Liu et al, 2018;Totterdell et al, 2008). In many cases, the SNS has been found to be related to particular traits of people's personality (Fang et al, 2015;Roberts et al, 2008;Selden & Goodie, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…63 Our results may reflect a neural embedding of such self-related affective valuation, perhaps accounting for the link between vmPFC macrostructure and adaptive social functioning and well-being. 181,182 Funding This work was funded by an ESRC PhD studentship and Wellcome Trust Institutional Strategic Support Fund…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no family‐based interventions that focus on cognitive health, but there are family‐based interventions that focus on health outcomes [37]. There is evidence on the benefits of stronger social networks and cognitive function using neuropsychological tests [38] and neuroimaging data [39]. Although educational attainment is considered to be static, there is an opportunity for adult educational programming and continued support for health educational opportunities.…”
Section: Discussionmentioning
confidence: 99%